1974
DOI: 10.1172/jci107835
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance in α and β Globin Synthesis Associated with a Hemoglobinopathy

Abstract: In contrast to findings in the thalassemia syndromes, studies of globin synthesis in subjects with structurally abnormal hemoglobins have generally revealed equal production of a and A polypeptide chains. However, in the present investigation of globin biosynthesis in vitro in blood and marrow from twoo subjects heterozygous for unstable hemoglobin Leiden, P66 or 7 Glu -* 0, a significant excess of a-chain production was revealed. A mother and daughter of northern European ancestry with mild compensated hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Imbalance in α and β globin chains has been greatly discussed in cases of thalassemias [ 33 35 ]. Altered α / β globin gene expression ratio in such cases is an important indicator of ineffective erythropoiesis as well as disease severity [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Imbalance in α and β globin chains has been greatly discussed in cases of thalassemias [ 33 35 ]. Altered α / β globin gene expression ratio in such cases is an important indicator of ineffective erythropoiesis as well as disease severity [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ,8:a ratios in these hemoglobins range from 0.8 to 0.9. For two of these hemoglobins (Hbs Koln and Abraham Lincoln), experimental evidence suggested that this slight imbalance in globin chain synthesis is the result of early degradation of the unstable a-chain (41,46 (31).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike prokaryotes which utilise operons to ensure the synthesis of related proteins in a coordinated manner, eukaryotes have a much more complicated cellular physiology which can lead to unassembled proteins [86,87]. The selective targeting of orphan proteins has been shown in the assembly of haemoglobin, a tetrameric complex composed of two α-globin subunits and two β-globin subunits, where mutations in haemoglobin result in dissociation of the complex and destruction of orphans to maintain proteostasis [88][89][90].…”
Section: Protein Complexesmentioning
confidence: 99%